2018
DOI: 10.1038/s41598-018-29919-0
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory-cued navigation in shearwaters: linking movement patterns to mechanisms

Abstract: After foraging in the open ocean pelagic birds can pinpoint their breeding colonies, located on remote islands in visually featureless seascapes. This remarkable ability to navigate over vast distances has been attributed to the birds being able to learn an olfactory map on the basis of wind-borne odors. Odor-cued navigation has been linked mechanistically to displacements with exponentially-truncated power-law distributions. Such distributions were previously identified in three species of Atlantic and Medite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Molossids are also known for their strong odors; males of many free-tailed bats species (including all four molossid species used in this study) develop gular-thoracic glands that may be used to mark females or roosting sites [78,79]. It is possible that even if these species are unlikely to be using olfaction as a sensory cue while foraging, they may use olfactory cues to find potential mates, or as homing cues during migration, as observed in some species of seabirds [80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…Molossids are also known for their strong odors; males of many free-tailed bats species (including all four molossid species used in this study) develop gular-thoracic glands that may be used to mark females or roosting sites [78,79]. It is possible that even if these species are unlikely to be using olfaction as a sensory cue while foraging, they may use olfactory cues to find potential mates, or as homing cues during migration, as observed in some species of seabirds [80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…Several successive studies, floating food odours on the sea surface and counting species approaching the odour source, confirmed that some petrel species are attracted by these cues that seem to help these seabirds in orientation towards the feeding areas (review in Roper 1999). Modelling studies on foraging tracks of shearwaters (Cory's shearwaters, Scopoli's shearwaters, and Cape Verde shearwaters, C. edwardsii) also suggested that their flight pattern is compatible with olfactory guidance (Reynolds et al 2015;Abolaffio et al 2018).…”
Section: Olfactory Navigation From the Model Species To Wild Birdsmentioning
confidence: 89%
“…Finally, for one of the archetypes used by CC, Diomedea calonectris , the motion of birds at large scales is not Brownian‐like diffusive as supposed by CC model, but on the contrary Lévy‐like super‐diffusive (Abolaffio, Reynolds, Cecere, Paiva, & Focardi, , and references therein).…”
Section: Weak Points In CC Modelmentioning
confidence: 99%